2016
DOI: 10.20964/101282
|View full text |Cite
|
Sign up to set email alerts
|

Sage Extracts as Inhibitors of Steel Corrosion in 4% HCl

Abstract: In this paper the research of corrosion protection of steel by processing corrosion environment using various concentrations of sage extracts (Salvia officinalis) (0.5 g/dm 3 , 1 g/dm 3 and 1.5 g/dm 3 ) in a 4% solution of HCl was carried out. Measurements were performed using gravimetric and electrochemical methods (Tafel extrapolation method and electrochemical impedance spectroscopy). The results have showed that sage is recommendable as a possible inhibitor in 4% solutions of HCl. The research also confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This is why a new group of natural corrosion inhibitors that have a potential to replace the synthetic ones is being investigated Several studies on the inhibition of corrosion of iron, steel, carbon steel by means of plant extracts (7)(8)(9)(10)(11) or purified compounds (12,13) have been recently conducted. Also, research has shown that Ficus tikoua leaves extract ( 14) is a good corrosion inhibitor for carbon steel under acidic conditions, Rosmarinus officinalis (7), Ginkgo (8), Aloe vera (10), Tinospora crispa (11), sage (15), bamboo (16), Thymus vulgaris (17), Eucalyptus (18) have been found to act as a very efficient inhibitor for iron or steel corrosion in acidic media. There is a great interest in using natural plant extracts or compounds that can act as cathodic or anodic corrosion inhibitors in neutral or acidic media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is why a new group of natural corrosion inhibitors that have a potential to replace the synthetic ones is being investigated Several studies on the inhibition of corrosion of iron, steel, carbon steel by means of plant extracts (7)(8)(9)(10)(11) or purified compounds (12,13) have been recently conducted. Also, research has shown that Ficus tikoua leaves extract ( 14) is a good corrosion inhibitor for carbon steel under acidic conditions, Rosmarinus officinalis (7), Ginkgo (8), Aloe vera (10), Tinospora crispa (11), sage (15), bamboo (16), Thymus vulgaris (17), Eucalyptus (18) have been found to act as a very efficient inhibitor for iron or steel corrosion in acidic media. There is a great interest in using natural plant extracts or compounds that can act as cathodic or anodic corrosion inhibitors in neutral or acidic media.…”
Section: Introductionmentioning
confidence: 99%
“…Nothing in literature has been found regarding the effect of sage as a natural inhibitor on tinplate corrosion. A research in potentiodynamic polarization has revealed that S. officinalis leaves extract (15) and sage essential oil (20) act as a green corrosion inhibitor of steel in acidic media. Sage (Salvia officinalis, Lamiaceae) contains naturally occurring phenolic dimers, flavonoids and plant oils.…”
Section: Introductionmentioning
confidence: 99%